(untitled) (American Journal of Innovation in Science and Engineering, 2025)
Expanding rapidly as a result of the expansion in digital banking transactions, modern modes of financial fraud have grown more complex, and traditional rule-based systems of detecting fraud have proved inadequate because of high false-positive rates (normally 15-20 percent), slow response times (greater than 30 seconds), and unchanging detection signatures. It has been shown that this is a key weak point in all financial systems around the world, leading to multi-billion dollar losses every year, with the expeditious creation of dynamic detection frameworks that can occur in real-time being needed. We mitigated this basic challenge by developing and deploying the first end-to-end data analytics and ensemble AI models solution to produce streaming data analytics applications entirely optimized to detect fraud in high-velocity transaction spaces (produces >3,000 transactions/second). We tested seven machine learning architectures including new temporal convolutional network (TCN) and gradient-boosted LSTM hybrids by conducting extreme experimentation with synthetic (PaySim) and real-world (n=2.1 million transaction records) data. The optimized system demonstrated record performance levels: 98.7 percent in detection accuracy (p<0.0001) and 0.8 percent false, and sub-second latency (mean latency=0.6s; SD=0.2), as well as 99.99 percent system uptime under peak traffic. More importantly, our adaptive learning module was proven to consistently improve over time, with 12.4% fewer false negatives recorded in a weekly re-training cycle. The ground-breaking findings bring a new level of the financial fraud prevention benchmark, providing the banking institutions with a ready-to-use solution that comfortably beats the established commercial systems by 22-35% on all key performance indicators while using 40% fewer computational resources. Streaming architecture and patented optimization techniques custom models of the framework create a paradigm shift in the field of financial cybersecurity that have initiate sweeping consequences to the universal banking safety standards and conformity regulatory environments.